2015
DOI: 10.1118/1.4906193
|View full text |Cite
|
Sign up to set email alerts
|

Breast dosimetry in transverse and longitudinal field MRI‐Linac radiotherapy systems

Abstract: Orienting the B0 magnetic field parallel to the photon beam axis, LRBP geometry, tends to restrict the radial spread of secondary electrons which resulted in dose reduction to the lung. Dosimetry issues observed in both Linac-MR geometries, such as changes to the lateral dose distribution, significantly exhibited dose reduction in the contralateral organs on a representative breast plan. Further, the results show sharper edge dose volume histogram curves at 1.5 T for both geometries, especially in the LRBP con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Current and developing machines make use of linac or 60 Co beam sources and have a range of magnetic fields strengths which are oriented either parallel or perpendicular to the incoming photon beam. The effect of the magnetic field is felt by the secondary electrons and has been shown to have a notable impact on patient dose distributions, particularly in regions of large density changes . Furthermore, the charge collected per MU in ion chambers has been shown to vary by several percent when making measurements in a magnetic field .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current and developing machines make use of linac or 60 Co beam sources and have a range of magnetic fields strengths which are oriented either parallel or perpendicular to the incoming photon beam. The effect of the magnetic field is felt by the secondary electrons and has been shown to have a notable impact on patient dose distributions, particularly in regions of large density changes . Furthermore, the charge collected per MU in ion chambers has been shown to vary by several percent when making measurements in a magnetic field .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the magnetic field is felt by the secondary electrons and has been shown to have a notable impact on patient dose distributions, particularly in regions of large density changes. [8][9][10] Furthermore, the charge collected per MU in ion chambers has been shown to vary by several percent when making measurements in a magnetic field. 11,12,13 The magnitude of the influence on the charge reading depends heavily on the ion chamber, beam quality, and on magnetic field magnitude and orientation with respect to the chamber and the photon beam.…”
Section: Introductionmentioning
confidence: 99%
“…28 Future work involves developing the phantom recipe further to include dosimetric gels in order to perform end-to-end testing and validate dose distributions derived from emerging technologies such as the MRI-Linac. 17,33,34…”
Section: Discussionmentioning
confidence: 99%
“…Current and developing machines are configured with magnetic fields ranging between 0.35 T and 1.5 T, with linac or Cobalt‐60 photon beams that are either parallel or perpendicular to the magnetic field. The magnetic field's effect on the trajectory of secondary electrons has been shown to affect dose distributions, particularly near interfaces between materials with very different densities . Furthermore, it has been found that the charge collected per MU in the ion chamber changes by plus or minus several percent in the presence of magnetic fields .…”
Section: Introductionmentioning
confidence: 99%